Asymmetries in Price-Setting Behavior: New Microeconometric Evidence from Switzerland - Kaufmann, Daniel; Honoré, Bo; Lein, Sarah (My University, 2012)
In this paper, we follow the recent empirical literature that has specified reduced-form models for price setting that are closely tied to (S, s)-pricing rules. Our contribution to the literature is twofold. First, we propose an estimator that relaxes distributional assumptions on the unobserved heterogeneity. Second, we use the estimator to examine the prevalence of positive price changes in a low-inflation environment. Our model estimates suggest that, if inflation falls from 0.9% to zero, the share of positive price changes in all price changes falls from 63.6% to 56.2%.
Keywords: Asymmetric price adjustment; menu costs; front loading; heterogeneity; CPI micro data; panel data